Penegakan Hukum Pertambangan dalam Pengembangan Sumber Daya Panas Bumi di Indonesia - Zidni Octafia Hafsah (Program Studi Ilmu Hukum, Universitas Kuningan, 2024)
Mining legal policy in the development of geothermal resources in Indonesia, with a focus on the case study of Decision Letter Number 489 K/Pdt.Sus-Pailit/2015. Indonesia has great potential in geothermal renewable energy which can be utilized to meet national energy needs. Through a normative juridical approach, this research analyzes legal policies governing the management of geothermal resources and their implementation in the context of legal disputes. The research results show that although there is a supportive legal framework, challenges in implementing and enforcing the law still exist, especially related to compliance with contractual agreements. The Supreme Court's decision in this case emphasizes the importance of fulfilling legal obligations by parties involved in geothermal exploitation, as well as the implications for sustainable natural resource management. It is hoped that this research will provide insight for the development of better policies in the renewable energy sector in Indonesia.